FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA PROGRAM STUDI AKUNTANSI - Will Andilla Darniaty; Mayta Tri Lestari; Siti Jumiyati (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2022)
This study aims to determine the factors that influence the level of accounting understanding of students in the accounting study program. The population used in this study amounted to 264 students with a total sample of 176 students. The sampling technique used the slovin formula. The variables studied include the competence of lecturers, emotional intelligence and learning styles. The method of data collection is by distributing questionnaires. Methods of data analysis using descriptive analysis and linear regression. The results showed that simultaneously lecturer competence, emotional intelligence and learning style had an effect on the level of accounting understanding of students in the accounting program. Partially, lecturer competence, emotional intelligence and learning style each have a significant positive effect on the level of accounting understanding of students in the accounting program.